2021
DOI: 10.1021/acs.est.1c03837
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Consequences of High Polychlorinated Biphenyl Exposure: Projected Decline of Delphinid Populations in a Hotspot for Chemical Pollution

Abstract: Rough-toothed dolphins, Steno bredanensis, are closely associated with coastal waters in the Southwestern Atlantic Ocean, increasing the exposure to multiple stressors, such as chemical pollution. Persistent organic pollutants (POPs) are known to affect the health of cetacean species. To comprehend the potential impacts of POPs on populations’ viability, it is necessary to distinguish populations and predict their risk of long-term exposure. Blubbers of rough-toothed dolphins (n = 28) collected along the south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…The relative contribution of POPs has been repeatedly used to distinguish cetacean aggregations within a geographic range (Borrell et al, 2006;Bruhn U et al, 1999;Hobbs et al, 2001;Lailson-Brito et al, 2012;de Oliveira-Ferreira et al, 2021;Santos-Neto et al, 2014). The detrended correspondence analysis (DCA) pointed to a differentiation between Guiana dolphins from the nine localities considered in this study (p = 0.0009; Fig.…”
Section: Differences Between Localitiesmentioning
confidence: 74%
See 2 more Smart Citations
“…The relative contribution of POPs has been repeatedly used to distinguish cetacean aggregations within a geographic range (Borrell et al, 2006;Bruhn U et al, 1999;Hobbs et al, 2001;Lailson-Brito et al, 2012;de Oliveira-Ferreira et al, 2021;Santos-Neto et al, 2014). The detrended correspondence analysis (DCA) pointed to a differentiation between Guiana dolphins from the nine localities considered in this study (p = 0.0009; Fig.…”
Section: Differences Between Localitiesmentioning
confidence: 74%
“…Its drainage basin counts 14 million habitants and over 12,000 industries of variate sorts (Kjerfve et al, 1997). A few other studies approached the contamination by organic pollutants in this bay and, repeatedly, the concentrations reported for marine fauna are found to be as high as heavily degraded areas from the Northern Hemisphere (Lailson-Brito et al, 2010;de Oliveira-Ferreira et al, 2021). Hence, marine mammals residing and/or using the bay are under exposure to multiple stressors.…”
Section: Differences Between Localitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies have been conducted on many aspects of the biology and ecology of this species (Azevedo et al, 2010; Bisi et al, 2013; Bittencourt, Barbosa, Santos‐Neto, et al, 2020; Caballero et al, 2013; Di Beneditto et al, 2001; Di Tullio et al, 2016; do Amaral et al, 2015; Dorneles et al, 2010; Lavandier et al, 2019; Leonel et al, 2012; Lima et al, 2016; Lopes et al, 2012; Méndez‐Fernandez et al, 2018, 2020; Moreno et al, 2005), information about habitat use, abundance, and behavior are scarce in SWAO. In southeastern Brazil cetaceans face several threats, such as chemical and noise pollution, habitat degradation, and bycatch (Bittencourt, Barbosa, Bisi, et al, 2020; Di Beneditto, 2003; Moreno et al, 2005; Oliveira‐Ferreira et al, 2021; Secchi et al, 2021), and Atlantic spotted dolphins are frequent in this region (Bisi et al, 2013; Moreno et al, 2005).…”
Section: Figurementioning
confidence: 99%
“…Halogenated aromatics are a class of particularly concerned pollutants due to their substantial emission into the environment, intrinsic properties akin to persistent organic pollutants, and lasting threats to health and the ecosystem. One well-known example is polychlorinated biphenyls (PCBs) that have been globally banned since 2001. However, recent studies still identified significantly high burdens of PCBs in marine mammals, collapsing the global population of killer whales by up to 50%. Meanwhile, huge quantities of less regulated emerging aryl halides, such as novel brominated flame retardants and polyhalogenated carbazoles, , have been loaded into the environment, which undermine our health and ecosystem further.…”
Section: Introductionmentioning
confidence: 99%